Comparison of Methods for the Purification of Alpha-1 Acid Glycoprotein from Human Plasma. (24th February 2011) - McCurdy, Teresa R.; Bhakta, Varsha; Eltringham-Smith, Louise J.; Gataiance, Sharon; Fox-Robichaud, Alison E.; Sheffield, William P.
Abstract : Alpha-1 acid glycoprotein (AGP) is a highly glycosylated, negatively charged plasma protein suggested to have anti-inflammatory and/or immunomodulatory activities. Purification of AGP could be simplified if methods that exploit its high solubility under chemically harsh conditions could be demonstrated to leave the protein in its native conformation. Procedures involving exposure of AGP to hot phenol or sulphosalicylic acid (SSA) were compared to solely chromatographic methods. Hot phenol-purified AGP was more rapidly cleared from mice in vivo following intravenous injection than chromatographically purified AGP. In contrast, SSA-purified AGP demonstrated an identical in vivo clearance profile and circular dichroism spectrum to chromatographically purified AGP. Similarly, no differences in susceptibility to enzymatic deglycosylation or reactivity with Sambucus nigra lectin were detected between AGP purified via the two methods. Incorporation of the SSA step in the purification scheme for AGP eliminated the need for a large (4 mL resin/mL of plasma) initial chromatographic step and simplified its purification without causing any detectable distortion in the conformation of the protein. Confirmation that this procedure is nondenaturing will simplify AGP purification and investigation of its possible biological roles in laboratory animals.